Rebuilding social relationships in contexts of refuge: spiritual kinship among Congolese in Kampala (Uganda) - Gusman, Alessandro (Journal of Eastern African studies, 2025)
This article examines how Congolese Pentecostal refugees in Kampala rebuild social relationships through the idiom and practice of spiritual kinship. Early studies of Pentecostalism emphasised individual and intergenerational rupture, and the weakening of kinship ties. The latter was interpreted as a way of freeing oneself from family obligations. Subsequent studies have nuanced the view, recognising that adherence to the new religion does not necessarily mean abandoning moral obligations to the kin group. Drawing on long-term ethnographic research with Congolese Pentecostals in Kampala, I show how spiritual kinship is (re)established in a refugee context, and the role shared religious affiliation plays in the way Congolese refugees engage in forms of ‘kin-work’, the affective and material labour of creating kinship-like relations, here mediated by shared faith. By analysing cases of adoption and hosting among Congolese families, the article highlights how Pentecostal idioms of relatedness enable refugees to envision continuity and shared futures amid protracted displacement. In doing so, it reformulates the question of what Pentecostalism does to kinship, asking instead what kinship does to Pentecostalism in the context of refuge.